Etapas de desarrollo en la planta de frijol - Fernández, F.; Gepts, Paul L.; López, M. (United Nations Development Programme, 1985)
The developmental scale of the bean crop and the general characteristics of plant development are described on the basis of morphological and physiological changes in the plant. The factors influencing the duration of the developmental stages of beans are identified, namely growth habit, earliness, and climate. (CIAT)